Banana chips (Musa acuminata) as an alternative lignocellulosic raw material for particleboard manufacture - Antonios Papadopoulos (Maderas: Ciencia y Tecnología, 2018)
This study shows that it is feasible to make one-layer experimental particleboards from banana chips.  Mechanical properties were easily satisfied at lower dosing rates, however thickness swelling remains a problem.  The addition of 1% wax to the boards bonded with 14% resin resulted in improved thickness swelling and satisfied the EN 312 standard, but still it was not sufficiently low to satisfy the ANSI standard.  It is suggested that combinations of banana chips with industrial wood chips, may be used in order to improve the thickness swelling of the particleboards.  Also, the use of chemical modification of the banana chips with conventional urea formaldehyde resin may be an avenue for exploration in further investigations.